Incidence, Risk Factors and Outcomes of Urinary Tract Infections in Renal Transplant Recipients – Prospective Observational Study - Jasmine Sethi; Shivakumar Patil; Suvarna Raju Chinege; Balwinder Mohan; Sarabpreet Singh; Manish Rathi; Deepesh Benjamin Kenwar; Ashish Sharma (Indian Journal of Transplantation)
Introduction: Urinary tract infections (UTI) are the most common infections following kidney transplantation. Risk factors for posttransplant UTI include female gender, advanced recipient age, pretransplant bladder abnormalities and posttransplant urinary tract instrumentation/stenting. Methods: This prospective observational study aimed to describe the incidence, risk factors, and graft outcomes in patients who developed posttransplant UTI at our program. All the patients who underwent renal transplant during the study were prospectively followed for 1 year. Results: Of 291 kidney transplant recipients, 31 developed UTI (10.6%). M: F ratio was 23:8 (74.2%:25.8%) with a mean age of 38.52 years (±14.5). Majority (n = 24, 77.4%) of patients were living donor-related transplants and 7 (22.59%) were cadaveric transplant recipients. The most common isolated organism was Escherichia coli in 20 patients (71.4%) followed by Klebsiella pneumoniae in 4 patients (14.3%). Piperacillin-tazobactam was the most commonly prescribed antibiotic in 7 patients followed by colistin and cefoperazone-sulbactam. Five out of 27 patients had multidrug-resistant organisms on culture (18.5%). Three patients expired during the study due to complications of UTI and the mortality rate was 9.6%. Mean serum creatinine rise during infection episode was 0.8 mg/dL (±0.7). Patients had a persistent mean serum creatinine rise of 0.17 attributable to the UTI episode (±0.63). The delta eGFR change (calculated by subtracting the baseline eGFR from the 1-month follow-up eGFR) was − 9.1 ml/min/1.73 m2. Conclusion: Around 10% of posttransplant patients in our study developed UTI. Factors significantly associated with acquiring UTI infection were the presence of diabetes (P < 0.001), posttransplant urine leak/stenting (P = 0.03), and pretransplant native kidney renal stone disease (P = 0.005). Apart from significant mortality (9.6%), posttransplant UTI leads to allograft dysfunction as represented by the mean persistent rise in serum creatinine of 0.17 mg/dl over the baseline serum creatinine.